Sociology of education - Boronski, Tomas; Hassan, Nasima (Los Angeles SAGE, 2015)
This textbook explains the basic principles of sociology and relates these concepts to today's society and education system in order to deepen your understanding of how these issues affect our lives and the world we live in, encouraging you to think critically and to develop a 'sociological imagination'.
Sociology and education studies -- Early sociology of education -- Developments in sociology of education -- Critical and radical pedagogies -- Differential educational attainment and the debate about intelligence -- Multiculturalism, 'race' and power -- Re-imagining gender roles -- Inclusion, disability and special educational needs -- The social construction of childhood -- Education policy -- Young people and pupil voice -- Transformations
Keywords: Educational sociology